Iturinic Lipopeptide Diversity in the Bacillus subtilis Species Group – Important Antifungals for Plant Disease Biocontrol Applications - Dunlap, Christopher A.; Bowman, Michael J.; Rooney, Alejandro P. (Frontiers in Microbiology, 2019)
Iturins and closely related lipopeptides constitute a family of antifungal compounds known as iturinic lipopetides that are produced by species in the Bacillus subtilis group. The compounds that comprise the family are: iturin, bacillomycin D, bacillomycin F, bacillomycin L, mycosubtilin and mojavensin. These lipopeptides are prominent in many Bacillus strains that have been commercialized as biological control agents against fungal plant pathogens and as plant growth promoters. The compounds are cyclic heptapeptides with a variable length alkyl sidechain, which confers surface activity properties resulting in an affinity for fungal membranes. Above a certain concentration, enough molecules enter the fungal cell membrane to create a pore in the cell wall, which leads to loss of cell contents and cell death. This study identified 330 iturinic lipopeptide clusters in publicly available genomes from the Bacillus subtilis species group. The clusters were subsequently assigned into distinguishable types on the basis of their unique amino acid sequences and then verified by HPLC MS/MS analysis. The results show some lipopeptides are only produced by one species, whereas certain others can produce up to three. In addition, four species previously not known to produce iturinic lipopetides were identified. The distribution of these compounds among the B. subtilis group species suggests that they play an important role in their speciation and evolution.